IVABRADINE THERAPY IN PATIENTS WITH CORONARY HEART DISEASE AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - N. A. Zheleznyakova; I. M. Sokolov; E. Ya. Gafanovich (Российский кардиологический журнал, 2012)
The combination of coronary heart disease (CHD) and chronic obstructive pulmonary disease (COPD) is widely prevalent in clinical practice. The problem of adequate therapy choice is important, since the majority of the medications administered in isolated CHD or COPD are contraindicated for the combination of these two disorders. In CHD patients with angina, heart rate (HR) control is one of the major methods to achieve the anti-anginal effect. In case of contraindications for beta-adrenoblockers or nondihydropyridine calcium channel blockers, the medication of choice is ivabradine.